Molecular and genomic insights into viral resistance in Capsicum spp.: pathogenesis, defense mechanisms, and breeding innovations - Shilpha, Jayabalan; Kang, Won-Hee (Frontiers in Plant Science, 2025)
Plant viruses represent a major challenge to agricultural systems, threatening global food security amid a rising population. Specifically, pepper cultivation (Capsicum annuum L.) is often hindered by various viral diseases, with more than 60 viruses identified as affecting pepper plants. The most efficient strategy for controlling viral diseases is the development of resistant cultivars of peppers. A comprehensive understanding of complex interactions between plant defense mechanisms and the strategies employed by viruses to evade these defenses, coupled with host factors that facilitate viral replication and movement, is essential for developing resistant cultivars. Natural antiviral defense mechanisms in plants are well characterized and include resistance genes, RNA silencing, autophagy-mediated degradation, translational repression, and resistance to viral movement. Recent advances in next-generation sequencing (NGS), genome-wide association studies (GWAS), high-density genotyping platforms and gene-editing tools such as CRISPR/Cas have accelerated the identification of resistance loci and key host factors involved in viral pathogenesis. This review summarizes current molecular and genomic insights into virus–host interactions in Capsicum spp., highlighting their role in advancing marker-assisted selection (MAS) and genomic-assisted breeding. The integration of molecular markers and genome editing into breeding pipelines offers new opportunities for developing durable, broad-spectrum viral resistance in peppers, ultimately supporting sustainable crop production and agricultural resilience.